Effects of low temperature on Chrysanthemum shiwogiku var. kinokuniense in vitro conservation (Bangladesh Journal of Botany, 2018)
The effect of low temperature condition on wild Chrysanthemum shiwogiku var. in vitro conservation was investigated, and its plant regeneration hereditary stability was detected using its sterile seedling. The results show that the test tube young plant grows rapidly, and its preservation time is short at a temperature at 25±2°C, at condition of 12 h/d, photoperiod at 2000 ~ 3000 lx, and all die after 180 days. However, the sterile seedling grows slowly under low-temperature, and its preservation time extends to 360 days. The sterile seedling surviving rate was above 96%. The data indicate that the 4°C low temperature is advantageous to Chrysanthemum plantlets preservation. After preservation, the recovered plantlets grow well and show no differences in morphology and isoenzyme zymogram of peroxidase, ISSR-PCR compared with the control. In addition, the results show that low temperature in vitro plantlets maintain genetic stability.